The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1080/21645515.2019.1578598
|View full text |Cite
|
Sign up to set email alerts
|

Genotype distribution and prevalence of human papillomavirus among women with cervical cytological abnormalities in Xinjiang, China

Abstract: Background: Genotype distribution and prevalence of human papillomavirus (HPV) among women vary from different regions and crowds, prophylactic HPV vaccin could prevent some diseases related to HPV, which include cervical precancerous lesions and cancer. Baseline surveys prior to mass HPV vaccination are critical to determine vaccine efficacy and detect changes in HPV type after vaccination. Objective: The aim of this study is to study the HPV type-specific prevalence in 698 women with cytological abnormalitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 41 publications
4
15
4
Order By: Relevance
“…In this study, 1658 cases (79.94%) were single HPV infections, and 416 cases (20.06%) were multiple HPV infections,which was in accordance with other studies 16 . Previous studies had reported the distribution of HPV genotypes was different among different regions.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, 1658 cases (79.94%) were single HPV infections, and 416 cases (20.06%) were multiple HPV infections,which was in accordance with other studies 16 . Previous studies had reported the distribution of HPV genotypes was different among different regions.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the prevalence of high-risk HPV in women with abnormal cytology was 52.1%, which is consistent with Northwest China (53.3%) [30] but there was a big gap with Northeast China (62.8%) [31]. In agreement with the previous study [1], women with high-risk HPV infection exhibited a high risk of cervical cytology abnormalities (Odd Ratio values range from 7.66 to 68.96).…”
Section: Plos Onesupporting
confidence: 91%
“…However, it is much higher than the prevalence of HPV infection found in Guyana (19.3%) [17], in the United States (15.2%) [18], in rural areas in Argentina (16%) [19] and in rural India (10.44%) [20]. However, it remains well below the prevalence found in China (54.87%) [21], Equatorial Guinea (60%) [22], Guinea Conakry (51.5%) [23], Kenya (44.3%) [24] and Nigeria (37%) [25].…”
Section: Prevalence Of Hpv Infection Among Respondents and Genotypingmentioning
confidence: 76%